The Effect of The Effectiveness of Market Retribution Management on Increasing Regional Retributions in Sumedang Regency - Susanti Suhendar; Fahrul Alam Masruri; Lilis Kartika (LPPM Universitas Sebelas April, 2022)
This study aims to determine the effect of the effectiveness of market retribution management on increasing regional levies at Bappenda Sumedang Regency. The method used in this study is a quantitative method with a survey research method approach. The population in this study were 87 market levy taxpayers. The data sources used were primary data and secondary data. Data collection techniques were obtained from questionnaires (google form) and from literature studies. Data analysis methods used data quality test, coefficient analysis, analysis simple linear regression, and hypothesis testing processed using the SPSS 25 application. The results of this study indicate that the Effectiveness of Market Retribution Management has a positive and significant effect on increasing regional or individual fees partially or individually, this is indicated by the value of t_count 4,588> t_table 1,988 with a significance level 0.000 <0.05